Women Harassment at Workplace: A Study of Pakistani Television Channels - Zia, Anjum; Batool, Sumera; Yasin, Zaeem (2016)
The present study explores the contemporary status of women harassment in Pakistani media industry taking alongside theoretical consideration of liberal feminism theory. An empirical method was adopted and in-depth interviews were conducted with media employees of both genders at television channels of the country. The study examined six core dimensions of harassment including working environment of the organization, male dominance, women harassment at workplaces, stereotype thinking patterns about women, offensive remarks on appearance of female colleagues and reporting of harassment issues to explore the current situation of women harassment in television channels of high repute. Findings of the study revealed that regardless of their ample role in thriving Pakistani media, women journalists are facing harassment at their workplaces but majority of them lesser likely to report harassment issues. Existence of stereotype thinking patterns about women and offensive remarks about appearance of women point towards severity of situation about women harassment at Pakistani media industry. Interestingly, despite male domination in media industry, general environment of media organizations is reported as satisfactory at large, whereas research concludes with highlighting areas for people working within and outside media organizations to eradicate harassment at workplaces. Keywords: Women harassment, male dominance, stereotype thinking patterns, Pakistani media, reporting of harassment.
Keywords: Myriam; Television